Improved Scalable Synthesis and Biological Activity of “Indoxyl-gal,” a Chromogenic Histochemical Used for the Identification of Lac+ Organisms - Banasik, Brent; Mai, Tam; Samadpour, Mansour (Letters in Organic Chemistry, 2018)
An improved and operationally simple synthesis of 3-indoxyl-β-D-galactopyranoside (indoxyl- gal) is disclosed. Indoxyl-gal is a sensitive chromogenic histochemical used for the identification of β-galactosidase enzymatic activity (lacZ gene). Synthesis of indoxyl-gal is improved to 25% overall yield in 5 linear steps from affordable starting materials with minimal chromatography. Biological testing confirmed the detection of β-galactosidase activity in all (100%, 19 strains) coliform bacteria using membrane filtration and modified MI agar.
Keywords: chromogenic dye